2012
DOI: 10.21608/ejp.2012.105286
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Studies on Fungal Diseases of Date Palm in New Valley Governorate

Abstract: uring seasons 2010/2011, leaf base rot, black scorch and inflorescences rot diseases have been observed on date palm trees and offshoot in nurseries and orchards of El-Kharga, Paris, El-Dakhla and El-Farafrah Oases in New Valley Governorate. Disease infection and severity (%) on date palm (var. Saidy) in the surveyed districts were found to be different. Several fungal species belonging to different genera were isolated from diseased samples collected from the surveyed districts. Frequency of the isolated fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
2
3
0
Order By: Relevance
“…divided isolates of Fusarium oxysporum into four clades Bryant and Moulton (2004);Dara et al (2023) Fusarium oxysporum, frequently isolated from symptomatic date palm tissues, was used for pathogenicity confirmation, and it fulfilled all steps of Koch's postulates. The study proved F. oxysporum, a pathogen causing wilt on date palm in Pakistan, and endorsed the findings of Louvet and Toutain (1981); Plyler et al (2000); Hernandez-Hernandez et al (2010);El-Morsi et al (2012), who also reported the same pathogen of this disease on date palms. However, the Etiology established in this study contradicts Maitlo et al (2009); Matlo et al (2021), who reported F. solani as a potential pathogen.…”
Section: Lesion Size (Cm)supporting
confidence: 88%
See 4 more Smart Citations
“…divided isolates of Fusarium oxysporum into four clades Bryant and Moulton (2004);Dara et al (2023) Fusarium oxysporum, frequently isolated from symptomatic date palm tissues, was used for pathogenicity confirmation, and it fulfilled all steps of Koch's postulates. The study proved F. oxysporum, a pathogen causing wilt on date palm in Pakistan, and endorsed the findings of Louvet and Toutain (1981); Plyler et al (2000); Hernandez-Hernandez et al (2010);El-Morsi et al (2012), who also reported the same pathogen of this disease on date palms. However, the Etiology established in this study contradicts Maitlo et al (2009); Matlo et al (2021), who reported F. solani as a potential pathogen.…”
Section: Lesion Size (Cm)supporting
confidence: 88%
“…This study revealed that disease is now prevailing in all the areas where the date palm has been growing across the country. The characteristic symptoms observed include chlorosis, one-sided yellowing, fronds killing, brown-colored stripes on the dorsal side of rachis, strikes on vascular bundles, and red discoloration on the roots, and these wilt disease symptoms were very similar to the typical symptoms of Fusarium wilt described by the other pathologists from various parts of the world (Maitlo et al 2009;Abdalla et al 2010;Abul-Soad, 2011;El-Morsi et al 2012 andNaheed et al 2023) Various species of Fusarium can cause wilts, i.e., F. solani, F. eumartii, F. avenaceum, F. tabacinum, and F. sulphureum, but F. oxysporum is mainly involved in causing wilts in a wide variety of important crops (Beckman 1987;Okungbowa and Shittu, 2012). This fungus comprises several important pathogenic and nonpathogenic species (Shishido et al, 2005).…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations